THE ATLAS OF EUROPEAN VALUES PROJECT: MAPPING THE VALUES OF EUROPEANS FOR EDUCATIONAL PURPOSES - Uwe KRAUSE (European Journal of Geography)
The European Values Study (EVS) is a large-scale, cross-national and longitudinal survey research programme on basic human values, initiated in the late 1970s. A product of this research is the Atlas of European Values (AoEV), published by the University of Tilburg in the Netherlands. This publication offers maps and background information about the opinions of the population in 46 European countries. The question was whether these materials have a potential for (geography) education. In a Comenius Project named European Values Education experts from different universities combined their experience in order to answer this question. They developed different map-tools and framework, background information, assignments, strategies, lesson plans and videos on how to deal with the maps and questions of the AoEV in an educational setting. All materials have been trialled in different countries and are available in 7 languages (English, Turkish, Dutch, German, French, Spanish and Slovak). They got a positive response from lecturers, teachers and students and can be used for courses about Europe, culture, citizenship and value-related issues and also meet the high standards of learning. They are available for free on the website www.atlasofeuropeanvalues.eu. This article summarises the basic findings of the European Values Study with respect to the theoretical frame. It discusses the geographical and educational contexts in which the developed materials and tools of the Atlas of European Values website can be used.